Dinamika Resiliensi Ibu Single parent dengan Anak Tuna Ganda - Uswatun Hasanah; Sofia Retnowati (Gadjah Mada Journal of Psychology (GamaJoP), 2017)
The purpose of this research is to assess the dynamics of resilience on single-parent mother who has a child with double-handicap, starting from the initial phase before and after the diagnosis of double-handicap, stress phase because of the escapement of husband and several risk factors that may arise, up to the phase of adaptation and strengthening. This research used the qualitative method by conducting observation and interview with three informants who domiciled in Kendari. The results showed that there are risk factors which become the initial process in the dynamics of resilience on single-parent mother who has a child with double-handicap, such as family dysfunction, financial and social problems, parenting stress on the mother and a belief that mystical factor was causing the problems. Those problems raised negative impacts on psychological and physical condition. The attempt made to solve the problems was centered on problem-focused coping and emotional focus coping by gaining support from the environment and doing daily activities. The processes of raising and strengthening of resilience on single-parent mother who has a child with double-handicap are also supported by protective factors such as hopefulness, learning from experience, the bond between child and mother, and religious belief.